WOMENPRENEUR MINDSET HOME INDUSTRY “ANEKA CEMILAN ASYIFAH ” IN THE DISTRICT OF RENGAT - Meilya Karya Putri (LPPM Press STIE Indragiri Rengat, 2022)
This study aims to determine how to develop the mindset of women entrepreneurs. This research is qualitative descriptive field research, because it wants to get a description of the Womenpreneur Mindset in the Home Industry